Iron-Catalyzed Conjugate Addition of Aryl Iodides onto Activated Alkenes under Air in Water - Chung-Min Huang (Catalysts, 2020)
The combination of commercially available FeCl3·6H2O with a water-soluble cationic 2,2′-bipyridyl catalytic system was found to enable the direct conjugate addition of aryl iodides onto activated alkenes, such as an α,β-unsaturated ester and a ketone, in a weakly acidic aqueous solution. This operationally simple protocol was carried out at 80 °C under air atmosphere in a potassium acetate-buffered aqueous solution for 12 h in the presence of Zn dust as a reductant to provide the desired 1,4-adducts in good yields.